Estimating sex by analyzing linear measurements of Brazilians’s dry skulls - Neves, Paulo Roberto; de Carvalho Cardozo, Ana Flavia; Andrade, Pedro de Sousa; Ulbricht, Viviane; Pereira Neto, João Sarmento; Francesquini Júnior, Luiz (Open Science Journal, 2021)
Brazilian forensic physical anthropology has developed substantially in recent years, thus, new regression models are being obtained and models proposed by international researchers are being validated, both in a national sample. This search is greatly significant for national forensic anthropology, due to our unique ancestral constitution, allowing for a gain in efficiency and reliability in the process of human identification. We sought to evaluate 12 linear measures, aiming to verify the existence of sexual dimorphism, as well as the possibility of developing a regression model to estimate sex. The researcher was properly trained and calibrated (ICC=0.95). After this stage, the data measured in 186 skulls (105 males and 81 females, with ages ranging from 18 to 80 years old, were analyzed. To perform the linear measurements, straight and curved digital calipers, duly calibrated, were used. According to the statistical analysis, all measurements performed are dimorphic. It was possible to build a logistic regression model for sex estimation. Notably, a sensitivity of 81.7% and specificity of 79.2% were found, with an accuracy of 80.65%. It was found that the logistic regression model obtained can be used as an auxiliary method in estimating sex in Brazilians.